Kolestaasi näitajate ja kõhulahtisuse seos intensiivavi haigetel - Kiss, Olga; Maizik, Jekaterina; Tamme, Kadri; Orav, Aivar; van de Poll, Marcel C.G.; Reintam Blaser, Annika (Eesti Arst, 2021)
Eesti Arst 2021; 100(1):56